Investigating Mental Health in Late Semester Adolescents in Higher Education in Jember: The Influence of Academic Stress and Emotional Intelligence - Nasruliyah Hikmatul Maghfiroh (West Science Interdisciplinary Studies, 2023)
Late-semester adolescents in higher education in Jember, Indonesia were studied to determine the effects of academic stress and emotional intelligence on their mental health. A cross-sectional design was adopted in this study, which included 450 teenagers in their final semesters from different universities. Data on academic stress, emotional intelligence, and mental health were gathered using standardized tests. Correlation, regression, and mediation analyses were performed statistically using SPSS software version 26. Academic stress needs to be addressed as a risk factor for mental health issues because the study indicated a significant positive association between it and poorer mental health. On the other hand, emotional intelligence was found to have a strong positive link with greater mental health, demonstrating its protective significance. Additionally, it was discovered that emotional intelligence somewhat mediates the link between academic stress and mental health. These findings highlight the significance of understanding the mental health issues late-semester adolescents in higher education encounter. To enhance emotion regulation and coping skills, institutions should offer specialized support services and think about including emotional intelligence training into their curricula. It is advised to conduct additional study on the efficacy of such programs as well as gender-specific interventions. Teenagers in Jember who are in their last semester can have better mental health if we handle academic stress and raise emotional quotient.